A weather diary from Donegal, Ireland, 1846–1875. (4th August 2020) - O'Connor, Stephen; Murphy, Conor; Butler, John; Crampsie, Arlene; Ludlow, Francis; Horvath, Csaba; Jobbová, Eva
Abstract : We present an overview of a weather diary for Glendooen, Co. Donegal in Ireland for the years 1846–1875. The record contains valuable direct observations of temperature and precipitation for the years 1864–1871, together with qualitative descriptions of weather covering the years of the Great Irish Famine and the exceptionally wet year of 1872.